Pengaruh Tax Avoidance terhadap Nilai Perusahaan dengan Adanya Insentif Tarif Pajak Badan Pasca COVID’19 (Studi Empiris Perusahaan LQ-45) - Zawitri, Sari; Yuliana, Elsa Sari; Kurniasih, Ninik (Journal of Economics, Bussiness and Management Issues, 2025)
This research proves the impact of the Tax Incentive policy, namely reducing the Corporate Income Tax (PPh) rate to 22%, on tax avoidance and its effect on company value post COVID’19. Type of comparative causal with secondary data from 45 LQ45 companies in 3 years (2020, 2021 and 2022). Data collection techniques were carried out using indirect observation and literature study. Sample using nonprobability sampling, purposive sampling technique, and simple linear regression analysis technique, the independent variable is tax avoidance and the dependent variable is company value. The results of the first problem show that there are 25 companies in 2021 and 18 companies in 2022 indicated to be evading taxes with the Cash ETR value decreasing. Then the results of the hypothesis test to answer the second problem, the significance (Sig) of Tax Avoidance (X) is 0.600, which is greater than the probability of 0.05, so there is no influence of the Tax Avoidance variable (X) on Company Value (Y). And the tax avoidance regression coefficient is – 0.059 which states that a 1% reduction in tax avoidance means the company value will decrease by – 0.059.